2015
DOI: 10.4103/0366-6999.157656
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Prognosis of End-stage Hypertrophic Cardiomyopathy

Abstract: Background:End-stage hypertrophic cardiomyopathy (HCM) is complicated by substantial adverse events. However, few studies have focused on electrocardiographic features and their prognostic values in HCM. This study aimed to evaluate the clinical manifestations and prognostic value of electrocardiography in patients with end-stage HCM.Methods:End-stage HCM patients were enrolled from a total of 1844 consecutive HCM patients from April 2002 to November 2013 at Fuwai Hospital. Clinical data, including medical his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
(51 reference statements)
0
16
0
Order By: Relevance
“…This was also confirmed in our study indicating that NYHA III/IV is an important prognostic factor for all-cause death (PAR = 7.79%) and cardiovascular death (PAR = 9.61%). In previous cohort studies, AF was reported to be a substantial risk factor for heart failure-related mortality and severe functional disability 12 , however, the significant relationship with AF disappeared in the multivariate model 16 , 27 . These results are in agreement with our study.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…This was also confirmed in our study indicating that NYHA III/IV is an important prognostic factor for all-cause death (PAR = 7.79%) and cardiovascular death (PAR = 9.61%). In previous cohort studies, AF was reported to be a substantial risk factor for heart failure-related mortality and severe functional disability 12 , however, the significant relationship with AF disappeared in the multivariate model 16 , 27 . These results are in agreement with our study.…”
Section: Discussionmentioning
confidence: 86%
“…Advanced heart failure (NYHA III/IV) was reported as an independent predictor of cardiovascular mortality in end-stage HCM 16 , as patients with heart failure at diagnosis showed a trend toward more frequent adverse outcomes, probably because they had more advanced disease 11 . This was also confirmed in our study indicating that NYHA III/IV is an important prognostic factor for all-cause death (PAR = 7.79%) and cardiovascular death (PAR = 9.61%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other less common causes are restrictive cardiomyopathies such as amyloidosis, constrictive pericarditis, cardiac tumors, and severe pulmonary hypertension. 10 Obstructive sleep apnea and obesity are independent risk factors for AF. 11 , 12 The electrical and structural remodeling determines the perpetuation of AF and the progression from paroxysmal to persistent and permanent forms.…”
Section: Pathophysiology Of Afmentioning
confidence: 99%
“…Hypertrophic obstructive cardiomyopathy (HCM) is a disease characterized by hypertrophy of the interventricular septum, obstruction of left ventricular outflow tract (LVOT), and frequently, systolic anterior motion (SAM) of the mitral valve. [ 1 2 3 ] Although medical intervention can provide relief of symptoms, a considerable number of patients with hypertrophic obstructive cardiomyopathy remain symptomatic, and in these participants, invasive interventions such as percutaneous transluminal septal myocardial ablation (PTSMA) and modified Morrow septal myectomy (MMSM) are established treatment options. [ 4 5 ] Extended septal myectomy can significantly relieve obstruction of LVOT and improve main complaints.…”
Section: Introductionmentioning
confidence: 99%